Against all odds : models of subversive spaces in National Socialist Germany - Petrescu, Corina L. 1976- (German life and civilization, 2010)
Introduction: Crypto-public domains within the Third Reich -- Ghettoöffentlichkeit : elements of subversiveness in the Jèudischer Kulturbund Berlin -- 1933 : Jewish fears and aspirations -- Under the spell of Nathan der Weise -- Reichsverband der Jèudischen Kulturbèunde in Deutschland -- Zionism in the Third Reich -- Reichsverband's Conference (September 5-7, 1936) -- Kristallnacht and its aftermath -- Kreisauer Kreis between deeds and thoughts -- Ideological roots -- The Kreisauer Kreis' coming together -- Passive Gegenöffentlichkeit -- Conspiratorial ties -- Cultural considerations -- The open protest of the Scholl-Schmorell-Kreis -- Emergence of the Scholl-Schmorell-Kreis -- The first phase of action : Flugblätter der Weissen Rose -- Russia's impact -- The second phase of action : Flugblätter der Widerstandsbewegung in Deutschland -- The third phase of action : Kommilitoninnen! Kommilitonen! -- Contemporary reactions to the Scholl-Schmorell-Kreis -- The anti-state activism of the Schulze-Boysen/Harnack Organisation -- Harro Schulze-Boysen's cultural heritage -- Pre-1933 political beliefs -- Gegner von heute Kampfgenossen von morgen -- Schulze-Boysen's activities, 1933-1939 -- Arvid Harnack and his group -- Coming together : Schulze-Boysen/Harnack Organisation -- The AGIS leaflets -- Alternative resistance actions -- Conclusion: Models to withstand